Implementasi Pembelajaran Terjemah Al-Qur’an Melalui Metode Granada bagi Santri Pondok Pesantren Ihyaul Qur’an Bengkulu Tengah - Sipangidoan Siregar , Renal; Satria, Irwan; Kurniawan (Yayasan Darusssalam Bengkulu, 2023)
This study aims to describe the Implementation of Al-Qur'an Translation Learning Through the Granada Method for Santri Ihyaul Qur'an Islamic Boarding School, Central Bengkulu. The Granada method encourages students to read and translate the Qur'an literally (words) according to the rules obtained during learning using the Granada method. This type of research is qualitative with a qualitative descriptive approach. The subjects and informants in this study were the Principal, Teachers and Students of Ihyaul Qur'an High School Bengkulu Tengah. The data collection technique uses observation, interview and documentation techniques. And data analysis is collected by data reduction, data display and conclusion drawing. The results showed that the implementation of Al-Qur'an translation learning through the Granada method for the students of the Ihyaul Qur'an Islamic Boarding School in Bengkulu Tengah was carried out once a week. Learning translation and interpretation of the Qur'an at the Central Bengkulu Ihyaul Qur'an Islamic Boarding School through the Granada method using the Silsilah Ta'lim Lughah Arabiyah book where at the beginning of the learning students are first given knowledge about sentence components in Arabic assisted by an Arabic dictionary -Indonesia and Ibn Kathir's Tafsir, so that the students can know the mufradat/vocabulary in words that are in the Al-Qur'an starting from Surah Al-Fatihah and then continuing to Juz 30 and this requires seriousness and continuous Istiqamah training with guidance and directions from asatidz.